In vitro fermentation of Cookeina speciosa glucans stimulates the growth of the butyrogenic Clostridium cluster XIVa in a targeted way. (1st March 2018) - Cantu-Jungles, Thaisa Moro; Ruthes, Andrea Caroline; El-Hindawy, Marwa; Moreno, Roberta Barbara; Zhang, Xiaowei; Cordeiro, Lucimara M.C.; Hamaker, Bruce R.; Iacomini, Marcello
Graphical abstract: Highlights: Two β-glucans from Cookeina speciosa were obtained and chemically characterized. They were submitted to an in vitro human fecal fermentation model. Both glucans were highly butyrogenic and propiogenic, with low gas production. Glucans promoted bacterial shifts distinct from fructooligosaccharides. Specific increases in genera from the Clostridium cluster XIVa were observed. Abstract: Dietary fiber chemical and physical structures may be critical to the comprehension of how they may modulate gut bacterial composition. We purified insoluble polymers from Cookeina speciosa, and investigated its fermentation profile in an in vitro human fecal fermentation model. Two glucans, characterized as a (1 → 3), (1 → 6)-linked and a (1→3)-linked β-D-glucans were obtained. Both glucans were highly butyrogenic and propiogenic, with low gas production, during in vitro fecal fermentation and led to distinct bacterial shifts if compared to fructooligosaccharides. Specific increases in Bacteroides uniformis and genera from the Clostridium cluster XIVa, such as butyrogenic Anaerostipes and Roseburia were observed. The (1 → 3)-linked β-D-glucan presented a faster fermentation profile compared to the branched (1 → 3), (1 → 6)-linked β-D-glucan. Our findings support the view that depending on its fine chemical structure, and likely its insoluble nature, these dietary fibers can be utilized to direct a targeted promotion of the intestinal microbiota to butyrogenic Clostridium cluster XIVa bacteria.